2021
DOI: 10.3389/fphar.2021.638622
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Transcriptome Analysis Identified a Novel Cancer Driver Genes Signature for Predicting the Prognostic of Patients With Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a common malignant tumor with high mortality and heterogeneity. Genetic mutations caused by driver genes are important contributors to the formation of the tumor microenvironment. The purpose of this study is to discuss the expression of cancer driver genes in tumor tissues and their clinical value in predicting the prognosis of HCC.Methods: All data were sourced from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), and Gene Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Some of these have documented roles in HCC development. For example, A1CF promotes NASH and HCC 64 , ESRP2 loss promotes HCC and lower expression predicts worse survival 32 , HNRNPAB induces EMT and promotes HCC metastasis 65 , the poly(C)-binding protein PCBP2 is upregulated in HCC and promotes proliferation 66 , SFPQ and RBM8A mediate resistance to platinum drugs in HCC 67 , 68 , RBMS1 blocks ferroptosis in HCC 69 , MATR3 promotes HCC progression 70 , SART3 is an immunotherapy target in HCC 71 , ZCRB1 is a signature gene for HCC 72 , and down regulation of CELF2 or CPEB3 promotes HCC 73 , but the targets for many of these splicing factors remain to be determined. The role of these splicing factors in early liver disease is less clear but mouse studies have highlighted a potential causative role for some splicing factors in the pathogenesis of NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these have documented roles in HCC development. For example, A1CF promotes NASH and HCC 64 , ESRP2 loss promotes HCC and lower expression predicts worse survival 32 , HNRNPAB induces EMT and promotes HCC metastasis 65 , the poly(C)-binding protein PCBP2 is upregulated in HCC and promotes proliferation 66 , SFPQ and RBM8A mediate resistance to platinum drugs in HCC 67 , 68 , RBMS1 blocks ferroptosis in HCC 69 , MATR3 promotes HCC progression 70 , SART3 is an immunotherapy target in HCC 71 , ZCRB1 is a signature gene for HCC 72 , and down regulation of CELF2 or CPEB3 promotes HCC 73 , but the targets for many of these splicing factors remain to be determined. The role of these splicing factors in early liver disease is less clear but mouse studies have highlighted a potential causative role for some splicing factors in the pathogenesis of NAFLD and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…In the precision medicine era, studies on genetic characteristics may provide us with new directions. A growing number of studies have proposed new biomarkers for liver cancer, such as the cancer driver gene [ 44 ], autophagy [ 45 ], and ferroptosis-related gene signature [ 46 ]. The present study identified novel transcriptional addiction gene-related signatures and nomograms.…”
Section: Discussionmentioning
confidence: 99%
“…All data from the TCGA and CGGA databases were transformed into log2 (x + 1) form for subsequent analyses. After that, the data on gene expression profiles from various databases were batchnormalized utilising the "Surrogate Variable Analysis (sva)" program that is included in R (Li et al, 2021). After intersecting all genes from the two datasets, 17,818 genes were defined as common genes.…”
Section: Introductionmentioning
confidence: 99%